FEATURES INNOVATIVE PROJECT MANAGEMENT IN THE CONSTRUCTION INDUSTRY - Malla Osman Mustafa (Статистика и экономика)
The article discusses the management ofproject activities, in terms of project management in the ﬁeld of innovation management features multifunctional work inconstruction, manufacturing, high-techindustry. The speciﬁcity of the activities ofthe classical and neoclassical approachesto the management of innovation projectsis reviewed. The main features and results of the multifactor model supportsmanagement of project activities for theimplementation of innovative applicationsare shown.